2022
DOI: 10.1002/anie.202200406
|View full text |Cite
|
Sign up to set email alerts
|

Overturned Loading of Inert CeO2to Active Co3O4for Unusually Improved Catalytic Activity in Fenton‐Like Reactions

Abstract: In the past decades, numerous efforts have been devoted to improving the catalytic activity of nanocomposites by either exposing more active sites or regulating the interaction between the support and nanoparticles while keeping the structure of the active sites unchanged. Here, we report the fabrication of a Co3O4−CeO2 nanocomposite via overturning the loading direction, i.e., loading an inert CeO2 support onto active Co3O4 nanoparticles. The resultant catalyst exhibits unexpectedly higher activity and stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…43‐1003). [ 16,18,20,23 ] Notably, the XRD patterns of Ce–Co 3 O 4 also exhibit diffraction peaks at 28.55°, consistent with the (111) planes of the CeO 2 phase (JCPDS No. 43‐1002).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…43‐1003). [ 16,18,20,23 ] Notably, the XRD patterns of Ce–Co 3 O 4 also exhibit diffraction peaks at 28.55°, consistent with the (111) planes of the CeO 2 phase (JCPDS No. 43‐1002).…”
Section: Resultssupporting
confidence: 54%
“…43‐1002). [ 20,23 ] The diffraction peaks of Ce–Co 3 O 4 display a slight shift toward lower angles compared to those of Co 3 O 4 , implying enlarged lattice spacings in Ce–Co 3 O 4 upon the introduction of Ce. Collectively, these findings confirm the successful incorporation of Ce atoms into the Co 3 O 4 crystal lattice.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the main reactive species, methanol (MeOH, radical scavenger for •OH and •SO 4 − ), ethanol (EtOH, radical scavenger for •OH), β ‐carotene (radical scavenger for 1 O 2 ), p‐benzoquinone ( p ‐BQ, a scavenger for •O 2 − ) are used as Fenton‐like reactions radical scavengers. [ 40 ] With the addition of EtOH and MeOH (Figure 3f), the degradation rate of NPX decreased sharply in both the Ru 2 N 6 ‐C/PMS system and the FeN 4 ‐C/PMS system. However, when β ‐carotene and p ‐BQ are used as quenchers, the degradation efficiency of NPX decreased slowly.…”
Section: Resultsmentioning
confidence: 99%
“…[41] Two major peaks in the O 1s spectra, located at around 529.75 and 530.81 eV (Figure 1f; and Figure S7d, Supporting Information), can be attributed to surface lattice oxygen species (O 2− , termed as O latt ) and surface-adsorbed oxygen species (such as O − and O 2 − , denoted as O ads ). [42,43] It is generally acknowledged that O ads species have far better reactivity and higher mobility, contributing more to the full oxidation of propane. [44] Based on the corresponding peak areas, the associated O ads species proportions in various catalysts were estimated, and the results revealed that Pt-Co 3 O 4 NPs/PFs catalysts had an O ads species ratio that was much greater than that of Co 3 O 4 NPs/PFs catalyst.…”
Section: Synthesis and Structure Characterization Of The Pt-co 3 O 4 ...mentioning
confidence: 99%